Characteristics of Tool Tilt Variation in Friction Stir Welding HDPE with Tool Made of 7075 Aluminum on Tensile and Bending Strengths - Nur Rochim, Mohammad; Darsono, Febri Budi; Kriswanto; Alkafi, Abu Faqih (Universitas Medan Area, 2025)
High-Density Polyethylene's (HDPE) potential is highlighted by the growing need for lightweight, high-strength materials in the automotive and aerospace industries. Friction Stir Welding (FSW) provides a solid-state joining method with low thermal degradation for producing high-quality joints in this thermoplastic material. With an emphasis on tensile and bending strength, this study attempts to examine how tool tilt angle variation affects HDPE joint quality. Three different tilt angle variations—0°, 1°, and 1.5°—were used in the experiment, which was carried out using an aluminum 7075 tool that was shaped like a grooved conical pin. A modified milling machine was used for welding, and ASTM D638 for tensile and ASTM D790 for bending mechanical tests were conducted. The findings show that the tilt angle has a major impact on the quality of the weld. With a tensile strength of 13 MPa (68.4% of raw HDPE), a bending strength of 16.5 MPa (70.5%), and a dense stir zone with few voids, the best weld was produced at a 1.5° angle. On the other hand, the weakest joint with obvious structural flaws was produced by the 0° angle. Overall, it is determined that the best tilt angle for improving the mechanical and aesthetic performance of FSW joints in HDPE is 1.5°.